PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS II SDN 008 PULAU RUMPUT - Raja Deni Wendri; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to improve student learning outcomes in science subjects (IPA) Class II SDN 008 Pulau Rumput through the implementation of cooperative learning model Type Student Team Achievement Dvision (STAD). The background research by the low learning outcomes of students in science subjects (IPA). That is because the model of learning or teaching style of teachers in presenting the material that tends to lecture and debriefing. As the subjects in this research were students of class II SDN 008 Pulau Rumput in 2014/2015 academic year with the number of students as many as 27 people consisting of 15 male students and 12 female students. The study design used is a Class Action Research. The stages are passed in PTK, namely: 1) Planning actions, 2) Implementation of the action, 3) observation, and 4) Reflection. The result of research in the application of cooperative learning Type Student Team Achievement Dvision (STAD) in science subjects is known that an increase in learning activities at each meeting. Increased activity of the students had a positive impact on student learning outcomes are likely to increase from a base score to the first cycle and into the second cycle. Before the act of student learning outcomes only reached an average of 64.4 to 44.4% classical completeness. In the first cycle the average student learning outcomes increased 23.9% from the base score to 79.8 to 77.8% classical completeness and the second cycle learning outcomes of students increased by 30.9% from the base score becomes 84.3 with classical completeness 96.3%. This situation shows that the improvement of learning in science subjects is successful, that the implementation of cooperative learning model Type Dvision Student Team Achievement (STAD) can improve IPA learning outcomes the student of class II SDN 008 Pulau Rumput.Keywords: Cooperative Learning Model Type Student Team Achievement Dvision (STAD), IPA Learning Outcomes